1994
DOI: 10.1007/bf02253435
|View full text |Cite
|
Sign up to set email alerts
|

Are NMDA antagonistic properties relevant for antiparkinsonianlike activity in rats?—Case of amantadine and memantine

Abstract: Amantadine (25, 50, 100 mg/kg), memantine (5, 10, 20 mg/kg) and MK-801 (0.05, 0.1, 0.2 mg/kg), all having NMDA channel blocking properties, were compared in three tests used for screening of antiparkinsonian agents in rats, namely: haloperidol-induced catalepsy, locomotor activity in monoamine depleted rats and rotation in rats with a unilateral substantia nigra lesion. Additionally, plasma levels of amantadine and memantine were assessed to gain an insight into the concentration ranges achieved at behaviorall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…Memantine (1-amino-3,5-dimethyladmantane) is an uncompetitive NMDA (N-methyl-D-aspartate) receptor antagonist (Kornhuber et al, 1989;1991;Bormann, 1989;Chen et al, 1992;Parsons et al, 1993;1995a, b) that has been used clinically for many years in the treatment of spasticity and to a lesser exent Parkinson's disease (Grossmann & Schutz, 1982;Wesemann et al, 1983;Schneider et al, 1984;Kornhuber et al, 1994;Danysz et al, 1994a;. More recently, doses of this compound predicted to act selectively at NMDA receptors in vivo have been found to produce symptomatological improvements in the therapy of dementia (Ditzler, 1991;G6rtelmeyer & Erbler, 1992;Pantev et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Memantine (1-amino-3,5-dimethyladmantane) is an uncompetitive NMDA (N-methyl-D-aspartate) receptor antagonist (Kornhuber et al, 1989;1991;Bormann, 1989;Chen et al, 1992;Parsons et al, 1993;1995a, b) that has been used clinically for many years in the treatment of spasticity and to a lesser exent Parkinson's disease (Grossmann & Schutz, 1982;Wesemann et al, 1983;Schneider et al, 1984;Kornhuber et al, 1994;Danysz et al, 1994a;. More recently, doses of this compound predicted to act selectively at NMDA receptors in vivo have been found to produce symptomatological improvements in the therapy of dementia (Ditzler, 1991;G6rtelmeyer & Erbler, 1992;Pantev et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The psychotropic mechanism of action induced by amantadine treatment has been thought to be due to N-methyl-D-aspartic acid (NMDA)-receptor antagonism, and other potent NMDA antagonist, MK-801, also induced hyperlocomotion in rodents (Löscher and Hönack, 1992) and hyperactivity in zebrafish (Chen et al, 2010). Although memantine, another NMDA antagonist, failed to induce hyperactivity in zebrafish (Chen et al, 2010), the false negative results in the present study for amantadine may be related to its potency for NMDA-antagonism (Wenk et al, 1995) or due to pharmacodynamic differences (Danysz et al, 1994). Cisplatin, an anti-cancer agent, occasionally induced seizures in patients (Steeghs et al, 2003), and there have also been reports indicating its potential to induce seizures at hyponatremic conditions (Cheng et al, 2011).…”
Section: Discussionmentioning
confidence: 50%
“…More recently, it has been shown that amantadine increases DA turnover in N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated mice (Rojas et al, 1993) and that it increases rat striatal AADC activity (Fisher et al, 1998). In addition, amantadine produces a uncompetitive blockade of the NMDA receptor (Danysz et al, 1994(Danysz et al, , 1997) that correlated well with the increases in striatal AADC activity (Hadjiconstantinou et al, 1995;Fisher et al, 1998). It may be postulated that the effect of amantadine may occur by at least two different mechanisms: increasing availability of DA, and low affinity uncompetitive blocking of NMDA-type glutamate receptors.…”
Section: Discussionmentioning
confidence: 98%
“…Amantadine is efficacious as a monotherapy and also exhibits a synergistic effect with levodopa and anticholinergics. It has been known for quite a number of years that the administration of amantadine to small rodents releases dopamine (DA) from striatal slices (Scatton et al, 1970), increases the brain DA outflow (von Voigtlander and Moore, 1970), and produces a low-affinity uncompetitive blockade of the n-methyl-D-aspartic acid (NMDA) receptor (Danysz et al, 1994).…”
Section: Introductionmentioning
confidence: 99%